อิทธิพลของอุณหภูมิที่อบต่อสมบัติทางเทอร์โมอิเล็กทริกของฟิล์มบางบิสมัสเทลลูไรด์ แบบบิดงอได้เตรียมโดยวิธีอาร์เอฟแมกนีตรอนสปัตเตอริง: Effect of Annealing Temperature on Thermoelectric Properties of Flexible Bi2Te3 Thin Film Prepared by RF Magnetron Sputtering - Singkaselit, Kamolmad; Sakulkalavek, Aparporn; Sakdanuphab, Rachsak (Asian Health, Science and Technology Reports, 2016)
งานวิจัยนี้ได้เตรียมฟิล์มบางบิสมัสเทลลูไรด์ (Bi2Te3) เคลือบลงบนวัตถุรองรับโพลีอิมมิด โดยใช้เทคนิคอาร์เอฟแมกนีตรอนสปัตเตอริง (RF magnetron sputtering) สมบัติเชิงโครงสร้างและสมบัติทางเทอร์โมอิเล็กทริกของฟิล์มถูกนำมาศึกษาภายใต้อุณหภูมิที่ใช้ในการอบ โดยนำฟิล์มบางบิสมัสเทลลูไรด์ที่ได้ไปอบที่อุณหภูมิแตกต่างกันตั้งแต่อุณหภูมิ 300, 350 และ 400 ºC ภายใต้ความดันบรรยากาศของก๊าซไนโตรเจนเป็นเวลา 1 ชั่วโมง โครงสร้างผลึกและโครงสร้างระดับจุลภาคของฟิล์มถูกนำมาวิเคราะห์ด้วยใช้เครื่องทดสอบการเลี้ยวเบนของรังสีเอกซ์ (XRD) และกล้องจุลทรรศน์อิเล็กตรอนแบบส่องกราดความละเอียดสูง (FESEM) ตามลำดับ ค่าสัมประสิทธิ์ซีเบคและค่าสภาพนำไฟฟ้าของฟิล์มถูกวัดตั้งแต่อุณหภูมิห้องถึง 150 ºC ด้วยเครื่องวัดค่าสัมประสิทธิ์ซีเบคและ ค่าสภาพนำไฟฟ้า (ZEM3) ผลการศึกษาพบว่าค่าสัมประสิทธิ์ซีเบคและค่าสภาพนำไฟฟ้าจะเพิ่มขึ้นเมื่ออุณหภูมิการอบเพิ่มขึ้น โดยการอบที่ 400 ºC จะมีค่าเพาเวอร์แฟกเตอร์สูงสุดคือ 1.41 x 10-3 W/m K2 วัดที่อุณหภูมิ 150 ºC Bismuth telluride (Bi2Te3) thermoelectric thin films were deposited on polyimide substrate by RF magnetron sputtering technique. The structural and thermoelectric properties of the films were investigated under the annealing temperatures. As-deposited films were annealed in the vacuum chamber with the N2 flow gases at three different temperatures of 300, 350, and 400 °C for 1 hour. The crystal structures and microscopy of the films were characterized by X-ray diffraction (XRD) and Field Emission Scanning Electron Microscope (FE-SEM), respectively. Seebeck coefficient and electrical conductivity of the films were simultaneously measured at room temperature and up to 150 °C by dc four-terminal method (ZEM3). It was found that the Seebeck coefficient and electrical conductivity increased with increasing temperature. The film annealed at 400 °C has a maximum PF value of 1.41 x 10-3 W/m.K2 at the applied temperature of 150 °C.